Study of temperature rise of a motor-driven implantable assist pump - MIKAMI, T; MITAMURA, Y; YASUDA, K; TOMODA, K; OKAMOTO, E; YAMAMOTO, K; ASADA, M (Jinko Zoki, 1994)
Temperature rise was studied in the motor-driven assist pump implanted in sheep and with a finite element methods (FEM) analysis. When the pump was implanted in fat with an actuator energy loss of 5.2W, postoperative temperatures were 41.0°C on the actuator surface and 39.5°C in the surrounding fat. In the case of an implantation of the pump between fat and skin with an actuator energy loss of 5.4W, the actuator surface temperature reached 40.5°C, and after that, the temperature gradually decreased until 39.2°C. The temperature distribution of the surrounding tissue was calculated with the FEM analysis. The analysis showed a possibility of a heat spot over 42°C on the actuator surface and low heat dissipation toward an inside body through a blood pump housing which is made of epoxy resin. Results of in vivo experiments showed that temperature rise of the motor-driven assist pump was within a safe level, but the FEM analysis suggested that more effective heat dissipation was required from the actuator to meet increase of energy loss with increase of pump output.